2008
DOI: 10.1007/s10555-008-9114-2
|View full text |Cite
|
Sign up to set email alerts
|

PTPL1: a large phosphatase with a split personality

Abstract: Protein tyrosine phosphatase, PTPL1, (also known as PTPN13, FAP-1, PTP-BAS, PTP1E) is a non-receptor type PTP and, at 270 kDa, is the largest phosphatase within this group. In addition to the well-conserved PTP domain, PTPL1 contains at least 7 putative macromolecular interaction domains. This structural complexity indicates that PTPL1 may modulate diverse cellular functions, perhaps exerting both positive and negative effects. In accordance with this idea, while certain studies suggest that PTPL1 can act as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 73 publications
(105 reference statements)
1
54
0
Order By: Relevance
“…Increased expression of miR-185 has also been observed in clear cell renal cell carcinoma compared to normal kidney tissues, and its expression is inversely correlated with its putative target PTPN13 (31). PTPN13 (protein tyrosine phosphatase, non-receptor type 13) is a Fas-associated protein tyrosine phosphatase and putative tumor suppressor gene that can inhibit PI3k/AkT signaling, suppress cell growth and induce apoptosis (32). Importantly, somatic PTPN13 mutations have been found in ~9% of CRCs (33), suggesting a critical role in the pathogenesis of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of miR-185 has also been observed in clear cell renal cell carcinoma compared to normal kidney tissues, and its expression is inversely correlated with its putative target PTPN13 (31). PTPN13 (protein tyrosine phosphatase, non-receptor type 13) is a Fas-associated protein tyrosine phosphatase and putative tumor suppressor gene that can inhibit PI3k/AkT signaling, suppress cell growth and induce apoptosis (32). Importantly, somatic PTPN13 mutations have been found in ~9% of CRCs (33), suggesting a critical role in the pathogenesis of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of PTPN13 in the Inhibitory Effect of Necl-2-It was reported that the protein-tyrosine phosphatase PTPN13 (also called PTPL1, FAP-1, PTP-BAS, and PTP1E), a known tumor suppressor (39), inhibits the ErbB2 activity by dephosphorylating the signal domain of ErbB2 and plays a role in attenuating the invasiveness and metastasis of ErbB2-overactive tumors (40). PTPN13 is a non-receptor type phosphatase with one FERM domain and five PDZ domains in addition to the catalytic domain (39).…”
Section: Involvement Of the Cytoplasmic Tail Of Necl-2 In Its Inhibitorymentioning
confidence: 99%
“…PTPN13 is a non-receptor type phosphatase with one FERM domain and five PDZ domains in addition to the catalytic domain (39). We therefore examined whether PTPN13 is responsible for the inhibitory effect of Necl-2 on the HRG-induced, ErbB2-catalyzed tyrosine phosphorylation of ErbB3.…”
Section: Involvement Of the Cytoplasmic Tail Of Necl-2 In Its Inhibitorymentioning
confidence: 99%
“…In the context of a study exploring the therapeutic opportunity of targeting Fap-1 is expressed at high levels in several tumor types [36]; its implication in cancer is complex and context-dependent being reported as either a tumor promoting or a tumor suppressor in different studies [23,42,44]. Interestingly, the recent identification of Fap-1 as a target of the epithelial-to-mesenchymal transition regulator miR-200c, which is lost during cancer progression, provides a mechanistic explanation for the early loss of sensitivity of cancer cells to CD95-mediated apoptosis during neoplastic transformation [45].…”
Section: Discussionmentioning
confidence: 99%